1989
DOI: 10.1039/c39890000473
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen species for the oxidative coupling of methane at lower temperatures

Abstract: The formation and reactivity of a stable oxygen species which is effective in the production of hydrocarbons from methane at lower than normal temperatures is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[1][2][3] Although they are often used only as high surface area supports to increase the dispersion of the active component, in some cases they are also known to participate directly in the catalytic reaction. We have chosen NiO as a model oxide both because of its interesting properties as a catalytic material 4,[8][9][10][11][12] and because it can be grown as thin crystalline films on various Ni foils and singlecrystal surfaces (Ni(110), [13][14][15][16] Ni(100), [17][18][19][20][21] Ni(111), 22,23 and others [24][25][26][27] ). Since real oxide catalysts usually consist of polycrystalline samples containing a variety of different lattice sites and metal oxidation states, it is difficult to derive a detailed picture about the contribution of each individual component to the overall reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Although they are often used only as high surface area supports to increase the dispersion of the active component, in some cases they are also known to participate directly in the catalytic reaction. We have chosen NiO as a model oxide both because of its interesting properties as a catalytic material 4,[8][9][10][11][12] and because it can be grown as thin crystalline films on various Ni foils and singlecrystal surfaces (Ni(110), [13][14][15][16] Ni(100), [17][18][19][20][21] Ni(111), 22,23 and others [24][25][26][27] ). Since real oxide catalysts usually consist of polycrystalline samples containing a variety of different lattice sites and metal oxidation states, it is difficult to derive a detailed picture about the contribution of each individual component to the overall reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore desirable to start the atomic-level characterization of oxides with well-defined surfaces in order to develop a better understanding of the role of both structure and oxidation states on their chemical properties. We have chosen NiO as a model oxide both because of its interesting properties as a catalytic material ,− and because it can be grown as thin crystalline films on various Ni foils and single-crystal surfaces (Ni(110), Ni(100), Ni(111), , and others ). The latter allows for the use of electron spectroscopic methods without having to deal with the charging problems that are typical in the study of insulating materials.…”
Section: Introductionmentioning
confidence: 99%
“…The effective catalysts and the mechanisms have been recently reviewed.2-4 There is a general consensus that the activation of methane on oxide catalysts is via the interaction of methane with surface-active oxygen species. [5][6][7][8] The studies on methane oxidative coupling proposed various models of methane activation depending on the different surface oxygen species involved in the hydrogen abstraction of methane. Otsuka and co-workers9•10 suggested that the active oxygen species for methane activation on Sm203 is a diatomic oxygen such as 022-.…”
mentioning
confidence: 99%